Challenges and Strategies of Classroom Management in Teaching and Learning at Elementary School - Munisa Imamah; Ari Purnawan; Rofiah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Classroom management is essential to ensure effective teaching and learning, especially at the elementary level where students’ behavioral, emotional, and cognitive development are still evolving. Although numerous studies have discussed classroom management techniques in general, limited research has focused on how elementary school teachers in post-pandemic contexts manage behavioral, motivational, and environmental challenges within diverse classroom settings. This gap highlights the need for deeper understanding of teachers’ real experiences and adaptive strategies in managing classrooms effectively. This study aims to identify the main challenges of classroom management and the strategies teachers use to address them. Using a qualitative descriptive approach, data were gathered from elementary school teachers through interviews, and analyzed using Miles and Huberman's framework. The results show that challenges arise from student factors (low motivation, disruptive behavior), teacher factors (limited training, workload), and environmental conditions (large classes, lack of facilities). Teachers responded with proactive strategies such as clear rules, positive reinforcement, engaging activities, and effective communication. The study concludes that successful classroom management requires adaptive, preventive, and responsive approaches aligned with students' developmental needs, offering both theoretical and practical contributions for improving learning environments.